Comparative Study of Refractive Errors Pre and Post COVID-19 Pandemic in Individuals with Increased Screen Time in the Age Group of 18-25 Years: A Literature Review - Shaikh, Nilofer M.; Nadgauda, Sameer S.; Raut, Ragini M. (Journal of Neonatal Surgery, 2025)
This literature review examines existing research on the comparative changes in refractive errors (such as myopia, hyperopia, and astigmatism) in young adults aged 18-25, related to increased screen time before and after the COVID-19 pandemic. With remote work, online education, and social isolation leading to prolonged exposure to digital devices, there is a growing concern regarding the impact of this lifestyle change on visual health. The review synthesizes findings from cross-sectional studies, discusses the potential mechanisms linking increased screen time to worsening refractive errors, and highlights gaps in the literature for future research directions.